Multiple-Choice Exams: An Obstacle for Higher-Level Thinking in Introductory Science Classes - Stanger-Hall, Kathrin F. (American Society for Cell Biology, 2012)
Learning science requires higher-level (critical) thinking skills that need to be practiced in science classes. This study tested the effect of exam format on critical-thinking skills. Multiple-choice (MC) testing is common in introductory science courses, and students in these classes tend to associate memorization with MC questions and may not see the need to modify their study strategies for critical thinking, because the MC exam format has not changed. To test the effect of exam format, I used two sections of an introductory biology class. One section was assessed with exams in the traditional MC format, the other section was assessed with both MC and constructed-response (CR) questions. The mixed exam format was correlated with significantly more cognitively active study behaviors and a significantly better performance on the cumulative final exam (after accounting for grade point average and gender). There was also less gender-bias in the CR answers. This suggests that the MC-only exam format indeed hinders critical thinking in introductory science classes. Introducing CR questions encouraged students to learn more and to be better critical thinkers and reduced gender bias. However, student resistance increased as students adjusted their perceptions of their own critical-thinking abilities.